Wave climate projections for Ireland for the end of the 21st century including analysis of EC‐Earth winds over the North Atlantic Ocean. (3rd February 2016) - Gallagher, Sarah; Gleeson, Emily; Tiron, Roxana; McGrath, Ray; Dias, Frédéric
ABSTRACT: This study aims to quantify the potential impact of global climate change on Ireland's marine resource, which is of significant economic and social importance. Global climate models predict warming of the Earth's atmosphere and oceans, which will consequently affect mean sea levels, the frequency and severity of extreme weather events, winds and ocean waves. Such changes need to be carefully assessed for long‐term marine and coastal planning. We derived future wave climate projections for Ireland using the EC‐Earth global climate model and the WAVEWATCH III wave model, by comparing the future 30‐year period 2070–2099 to 1980–2009 for the RCP4.5 and the RCP8.5 forcing scenarios. This data set is currently the highest resolution wave projection data set available for Ireland. EC‐Earth predicts decreases in means (up to 3%) and extremes (up to 14% for the 95th percentile) of 10 m wind speeds over the North Atlantic Ocean (5–75°N, 0–80°W) by the end of the century. Similarly, the model projections show decreases in the frequency and intensity of wind storms crossing Ireland but these changes are not statistically significant. The WAVEWATCH III model predicts an overall decrease in mean (up to 15%) and extreme (up to 15% for the 95th percentile) annual, boreal winter and summer significant wave heights around Ireland.